1H NMR-based dynamic metabolomics delineates the therapeutic effects of Shenfu injection on laparoscopic hysterectomy. Issue 52 (24th December 2020) - Wang, Xue; Wang, Kai; Wang, Huan; Li, Xiangkui; Feng, Jinzhou; Chen, Qian
Abstract : Abstract: To explore the effect and mechanism of Shenfu Injection on serum metabolomics in laparoscopic hysterectomy. 1.5 mL/kg Shenfu injection was added to inject 200 mL of normal saline after the patients who entered the standard were admitted to the operating room. NMR metabolomics were performed at each time point before anesthesia (T0), immediately after pneumoperitoneum (T1), and at the end of surgery (T2). Multivariate trajectory analysis showed that SFI treatment could make laparoscopic hysterectomy interfere with the recovery of plasma metabolites to normal metabolic state, with a time-dependent trend. In addition, the key metabolic changes of laparoscopic hysterectomy at different stages of SFI treatment involve energy metabolism, oxidative stress response, amino acid metabolism, and pyruvate metabolism. Especially, the important role of SFI in the treatment of laparoscopic hysterectomy is antioxidant capacity. The results show that SFI can be used as a potential drug for laparoscopic hysterectomy. The current findings provided, for the first time, sound evidence of the protective effects of SFI on laparoscopic hysterectomy from both biochemical and metabolomics perspectives. The mechanisms of SFI could be related to regulating amino acid metabolism, pyruvate metabolism, and energy metabolism. The present study lays an important foundation for further research and for the broad clinical application of SFI.